Aspects of soil fertility and nutrition of Pinus taeda L: A review - Kulmann, Matheus Severo de Souza; Dick, Grasiele; Araujo, Maristela Machado; Brunetto, Gustavo; Schumacher, Mauro Valdir (Revista Ecologia e Nutrição Florestal - ENFLO, 2023)
The cultivation of the genus Pinus spp. in Brazil occupies an area of 1.7 million hectares in 2020. Pinus is considered a socioeconomic component, which helps maintain the development of the southern region of the country and the national supply chain. However, the areas destined for pine cultivation usually have acidic soils and low natural fertility, which reduces the nutrients availability, negatively influencing the crop development. However, it is not known if Pinus responds positively to mineral fertilization, nor what is the nutrient of greatest demand regarding plantation development. Thus, the objective of this review is to explore which nutrients are of greatest nutrient need and therefore most responsive to pine growth and productivity. Thus, this review aims to establish a discussion on the importance and current plantation of Pinus taeda, along with answers on fertilization and nutrition of the crop, obtaining data from articles found in scientific databases of international literature, to better inform fertilization practices for this little studied crop. We have seen that mineral fertilization aims to optimize the pine growth, seeking to meet the physiological needs of the plants and thus achieve maximum crop productivity. However, the literature shows that many times the pine does not respond expressively in growth when subjected to mineral fertilization. Thus, studies that consider the effects of nutrient application to the pine crop, over time, are required to better conclude whether the pine crop responds to the nutrient supply.